2017
DOI: 10.1111/crj.12602
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic evaluation by oxygenation with positive end‐expiratory pressure in acute exacerbation of idiopathic pulmonary fibrosis: A retrospective cohort study

Abstract: Evaluation of oxygenation with PEEP may provide useful information for predicting short-term mortality in patients with AE-IPF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 30 publications
1
13
0
Order By: Relevance
“…Higher serum D‐dimer and lower PaO 2 /FiO 2 ratio at the time of diagnosis of AE were independent predictors of 90‐day mortality in AE‐ILD. Previous studies have shown the prognostic utility of these variables using the data of AE‐IPF based on the 2007 definition . We now demonstrated the same results using the 2016 definition.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Higher serum D‐dimer and lower PaO 2 /FiO 2 ratio at the time of diagnosis of AE were independent predictors of 90‐day mortality in AE‐ILD. Previous studies have shown the prognostic utility of these variables using the data of AE‐IPF based on the 2007 definition . We now demonstrated the same results using the 2016 definition.…”
Section: Discussionsupporting
confidence: 81%
“…Idiopathic pulmonary fibrosis (IPF) is a progressive and devastating disease with a median survival time (MST) of 3–4 years after diagnosis . The majority of patients with IPF demonstrate a gradual worsening over years, but a significant minority of patients experience episodes of acute respiratory worsening, termed acute exacerbation (AE) . In 2016, an international working group revised the definition and diagnostic criteria for AE‐IPF .…”
Section: Introductionmentioning
confidence: 99%
“…This is because the molecular weight of SP‐D is less than that of KL‐6, and SP‐D in alveolar spaces might flow into the blood stream more easily and thus better reflect AE‐IIPs disease activity than KL‐6. However, the prognostic significance of serum KL‐6 for AE‐IPF has also been previously reported …”
Section: Discussionmentioning
confidence: 93%
“…However, the prognostic significance of serum KL-6 for AE-IPF has also been previously reported. 36,37 There are some limitations in this study. First, this is a retrospective study conducted at a single institute.…”
Section: Discussionmentioning
confidence: 96%
“…For IPF patients suffering from hypoxic respiratory failure, HFNC is a non-invasive approach to relieve hypoxia and permit physical activity. Patients in whom HFNC is insufficient may benefit from invasive mechanical ventilation through recruitment of atelectatic lung and improved ventilation-perfusion matching (46). However, mechanical ventilation in IPF patients is not without risk.…”
Section: Pulmonary Arterial Hypertensionmentioning
confidence: 99%